Analisis Faktor yang Mempengaruhi Kinerja Personel DITRESKRIMSUS Polda Lampung: Analysis of Factors Influencing the Performance of Personnel of the Lampung Regional Police's Special Criminal Investigation Directorate - Ida Elvida Wati; RZ Abdul Aziz (Jurnal Bisnis dan Ekonomi, 2026)
Objective: The purpose of this study is to analyze several factors that may influence the performance of personnel at the Lampung Regional Police's Criminal Investigation Directorate. Methodology: This study employed a multiple linear regression approach using SPSS 26. Research Results: The estimated results indicate that motivation is a variable with a positive and significant influence on personnel performance. The work environment also influences personnel performance, although its significance is at a looser tolerance level of 10%. Workload and competency variables do not significantly influence personnel performance.